Correlation Between SUA and Prognosis in CHF Patients After Revascularization: SUA and Prognosis in CHF Patients After Revascularization - Miao, Bo; Wu, Jing; Wang, Jiao; Li, Yanxin; Da, Yingxiao; Wang, Dong; Gao, Bei (Journal of Medical Biochemistry, 2023)
Background: To explore the correlation between serum uric acid (SUA) and prognosis in patients with chronic heart failure (CHF) after revascularization. Methods: A total of 126 patients with CHF undergoing revascularization [coronary artery intervention (PCI) or coronary artery bypass grafting (CABG)] in the hospital were enrolled as CHF group between December 2021 and October 2022, while 126 healthy controls during the same period were enrolled as healthy control group. The levels of SUA, inflammatory factors and cardiac function in the two groups were detected. The correlation between SUA level and inflammatory factors, cardiac function levels was analyzed. All patients in CHF group were followed up for 6 months to observe prognosis. The differences in the above indexes among patients with different prognosis were compared. The risk factors of prognosis were analyzed by multivariate Logistic regression analysis, and their predictive value for prognosis was evaluated by ROC curves analysis. Results: SUA, IL-6, TNF-α, NT-proBNP and LVEDD in CHF group were higher than those in healthy control group, while LVEF was lower than that in healthy control group (P
Keywords: Serum uric acid; Revascularization; Chronic heart failure; Prognosis; Correlation; Cardiac function